AN ASSESSMENT OF INDIAâ€™S ABORTION LAWS: CRITICAL INSIGHT - et. al., Sunishtha Moghe (International Journal of Modern Agriculture, 2021)
The primary and only â€˜abortionâ€™ law in India i.e., â€œMedical Termination of Pregnancy Act, 1971â€, governs the rights of women with respect to the termination of their pregnancy. Although, considered progressive for the time it was legislated, the law hasnâ€™t been amended since then and poses many questions with regard to not only its implementation but provisions that are seen as irrelevant and outmoded. According to a 2015 Guttmacher Institute Report an estimated 78% of medical terminations in India were procured outside of state authorized health centres. Keeping in view the inaccessibility of abortion related services in India, providing a legal support structure that eases the process remains imperative for improving the health structure of the country. While the newly tabled â€œMedical Termination of Pregnancy (Amendment) Bill, 2020â€ is most certainly a reformed version of the incumbent act, a lot is still needed to be improved â€“ and it is most certainly warranted by the people of India. The Bill is undeniably reformative and comparatively inclusive, yet by refraining from decriminalising abortion and recognising it as a right, it fails to realise the constitutional vision